2019
DOI: 10.2147/ndt.s203513
|View full text |Cite|
|
Sign up to set email alerts
|

<p>A patient with Korsakoff syndrome of psychiatric and alcoholic etiology presenting as DSM-5 mild neurocognitive disorder</p>

Abstract: Background: Wernicke’s encephalopathy (WE) and Korsakoff syndrome (KS) are underdiagnosed. The DSM-5 has raised the diagnostic threshold by including KS in the major neurocognitive disorders, which requires that the patient needs help in everyday activities. Methods: We report clinical, neuropsychological, and radiological findings from a patient who developed Wernicke-Korsakoff syndrome as a result of alcohol use and weight loss due to major depression. We assess the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Studies on patients suffering from the Korsakoff syndrome have reported that a reduction in mammillary bodies, thalamus, hypothalamus, basal ganglia, cerebellar vermis and damaged white-matter tracts (partially in genu of the corpus callosum) was responsible for a set of higher-order cognitive dysfunctions, including verbal working memory, immediate and delayed verbal recall, verbal and visual recognition, executive functions, but in attention processes the difficulties was not observed [68]. However, in spite of unclear regional brain dysfunction, verbal memory disorder was seen especially in patients with Korsakoff's syndrome, but not in the non-demented alcoholic patients [69].…”
Section: Structural Changes In the Brain Related To Memory Disorders ...mentioning
confidence: 99%
“…Studies on patients suffering from the Korsakoff syndrome have reported that a reduction in mammillary bodies, thalamus, hypothalamus, basal ganglia, cerebellar vermis and damaged white-matter tracts (partially in genu of the corpus callosum) was responsible for a set of higher-order cognitive dysfunctions, including verbal working memory, immediate and delayed verbal recall, verbal and visual recognition, executive functions, but in attention processes the difficulties was not observed [68]. However, in spite of unclear regional brain dysfunction, verbal memory disorder was seen especially in patients with Korsakoff's syndrome, but not in the non-demented alcoholic patients [69].…”
Section: Structural Changes In the Brain Related To Memory Disorders ...mentioning
confidence: 99%
“…ARBD is a substantial public health concern, and yet research suggests that there is currently a lack of knowledge and understanding of ARBD amongst both the general public and, perhaps more importantly, health‐care professionals [ 9 , 10 ]. This is reported to have resulted in individuals going undiagnosed and, in some cases, misdiagnosed [ 11 , 12 , 13 ] and therefore untreated [ 14 , 15 ]. There is evidence that ARBD is not a degenerative condition and research also suggests that not only can it be prevented with adequate support, but also that those with the condition have the potential to improve and even reverse their symptoms if recognised early in the disease trajectory and managed promptly [ 16 ].…”
Section: Introductionmentioning
confidence: 99%